Primary Pulmonary Sarcoma Coinfected with Pulmonary Tuberculosis: A Case Report - Dea Putri Audina; Sita Laksmi Andarini; Hana Khairina Putri Faisal; Prasenohadi Prasenohadi; Jamal Zaini; Herawati Hidajat (http://dharmais.co.id/, 2023)
Introduction: Pulmonary tuberculosis (TB) and malignancy are conditions with similar respiratory diseases and they are even known to coexist simultaneously. Therefore, accurate diagnosis of each disease is crucial to ensure precise treatment. This case study showed the coexistence of pulmonary TB and primary pulmonary sarcoma.Case Presentation: A 62-year-old male presented with a 3-month history of dyspnea, which worsened within 3 days. Before hospitalization, there were complaints of left chest pain, fatigue, loss of appetite, weight loss within 5 months, and night sweats. The patient who was a heavy smoker had experienced hemoptysis in the past 5 months. Upon physical examination, an increased respiratory rate and decreased oxygen saturation level. Furthermore, there were asymmetrical thorax movements, dull percussion on the left side, and decreased vesicular breathing sound on the left hemithorax, with no rhonchi or wheezing. A chest x-ray showed a destroyed left lung, while scanning confirmed left lung atelectasis and indicated a suspected mass within or around the left bronchus causing total obstruction in the main left bronchus. The bronchoscopy procedure identified a mass blocking the left main bronchus. However, a biopsy yielded inconclusive results. A rapid molecular test of TB detected Mycobacterium tuberculosis, which was discovered to be Rifampicin sensitive. As a result, the patient was treated daily with 4 fixed drug combinations for anti-TB. Despite the treatment, the complaint was not resolved within the next 3 months, as there was still a disease of cough in the form of mass-like phlegm, which uncovered a malignancy focus cell with differential diagnosis of pleomorphic sarcoma and sarcomatoid carcinoma.Conclusions: Lung malignancy not only overlapped with but also occurred simultaneously alongside lung TB. Therefore, it was crucial to establish a clear diagnosis in patients with chronic respiratory disease.